An Evaluation on Plan and Facade Compositions in Architect Kemaleddin's Educational Buildings - Köksalan, Zeynep İldeniz; Şahin, Murat (Gazi Üniversitesi, 2024)
Architect Kemaleddin, one of the pioneers of the idea of creating a National Architecture, took part in the design of many buildings with different typological features. During his most productive years, he designed many school buildings. The design approach adopted in the production of plans and facades has been defined as the "Kemaleddin School". In the study, better understanding the plan and facade style of Kemaleddin's educational buildings was determined as the research subject. Within the scope of the study, the Reşadiye School, Sultan Abdülhamid-i Evvel Madrasa, Medreset-ül Kuzat, Bostancı İbrahim Paşa Primary school, Göztepe Primary school and Gazi Education Institute buildings designed by Architect Kemaleddin were evaluated. It is aimed to evaluate the typological similarities and differences of the plans and facades of Kemaleddin's educational buildings by creating tables. As a result of the study, the frequent occurrence of rectangular, L and U-shaped plan layouts and the presence of protrusions that emphasize the entrance were determined to be common features of the buildings. It gives the impression that the facade design is designed in vertical and horizontal parts and that there is a rhythmic order. Especially the use of rectangular and pendant arched molded windows with different shapes between the floors and the wide eaves roof form were observed as characteristic features of educational buildings.
Keywords: Architectural History; Theory and Criticism; Mimari Tarih; Teori ve Eleştiri